ORGANIZATION OF INDEPENDENT WORK OF STUDENTS IN THE PROCESS OF OBTAINING VOCATIONAL EDUCATION - Bobkova Іnna; Burianova, Viktoriia; Honcharuk , Svitlana; Uminska , Kateryna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article examines various forms of organizing independent work of students during teaching of professional disciplines. The feasibility of using interactive technologies in the educational process is argued. It has been proven that independent work of students is the main means of mastering educational material in time free from mandatory classes.